Echocardiographic assessment of suspicious clinical and electrocardiogram findings of healthy young male military aspirants: a cross sectional observational study - Paudel, Navaraj; Alurkar, Vijay Madhav (Journal of College of Medical Sciences-Nepal, 2018)
ABSTRACT Background: Heavy exercise is associated with multiple physiological changes in cardiovascular system. Individuals who otherwise are healthy and asymptomatic are also found to have cardiac abnormalities. The aim of study is to find prevalance of structural abnormalities in apparently healthy males who are found to have abnormal/ suspicious clinical/electrogram findings during routine screening. Materials and Methods: A cross-sectional study was done in the department of cardiology within Manipal Teaching Hospital, Pokhara over a period of 3 years (December 2013 to December 2016). The study population included all the participants who were apparently healthy young males competing for military recruitment. After the initial screening, those who had abnormal/suspicious findings in the physical examination or in ECG were subjected for trans-thoracic echocardiogram to assess for any structural abnormality Results: Out of 1950 individuals, who underwent physical examination and ECG, 165 had abnormal physical findings and 261 had abnormal ECG findings (21.84% of total had any form of abnormality). 72 (43%) had grade 2 short systolic murmur in the pulmonary area followed by pansystolic murmur in apex. Only 1.8% had diastolic murmur in aortic area. Most common ECG abnormality found was LVH followed by sinus bradycardia and Tinversion in III . Almost 7% of individuals with abnormal ECG findings. Only 16 (0.82% of the total screened/ 4.38% of suspicious findings) had structural abnormalities in echocardiography: 12 had RHD (MR-7, AR-3, R+AS+MR=2); 1 had ASD, 1 had VSD, 1 had Ebstein’s anomaly and 1 had mild valvular pulmonary stenosis (congenital). Conclusion: Individuals who are otherwise healthy and asymptomatic were found to have cardiac abnormality (almost 1.7% had serious electrical or structural abnormality). Cardiovascular screening of all the individuals seeking jobs requiring intense physical exertion is essential to prevent serious cardiovascular outcomes. Keywords: echocardiography; electrocardiography; intense exercise; physical cardiac findings.